Characterization of heme environment and mechanism of peroxide bond cleavage in human prostacyclin synthase - Yeh, Hui-Chun (2005)
Prostacyclin is a potent mediator of vasodilation and anti-platelet aggregation. It is synthesized from prostaglandin H(2) by prostacyclin synthase (PGIS), a member of Family 8 in the cytochrome P450 superfamily. Unlike most P450s, which require exogenous reducing equivalents and an oxygen molecule for mono-oxygenation, PGIS catalyzes an isomerization with an initial step of endoperoxide bond cleavage of prostaglandin H(2) (PGH(2)). The low abundance of PGIS in natural tissues necessitates heterologous expression for studies of structure/function relationships and reaction mechanism. We report here a high-yield prokaryotic system for expression of enzymatically active human PGIS. The PGIS cDNA is modified by replacing the hydrophobic amino-terminal sequence with the more hydrophilic amino-terminal sequence from P450 2C5 and by adding a four-histidine tag at the carboxyl terminus. The resulting recombinant PGIS associates with host cell membranes and was purified to electrophoretic homogeneity by nickel affinity, hydroxyapatite and CM Sepharose column chromatography. The recombinant PGIS, with a heme:protein ratio of 0.9:1, catalyzes prostacyclin formation at a K(m) of 13.3 µM PGH(2) and a V(max) of 980 per min. The dithionite-reduced PGIS binds CO with an on-rate of 5.6 × 10(5) M(−1) s(−1) and an off-rate of 15 s(−1). The ferrous–CO complex of PGIS is very short-lived and decays at a rate of 0.7 s(−1). Spectral binding assays showed that imidazole binds weakly to PGIS (K(d) ~0.5 mM,) but clotrimazole, a bulky and rigid imidazole derivative, binds strongly (K(d) ~1 µM). The transient nature of the CO complex and the weak imidazole binding seem to support an earlier proposal that PGIS active site has a limited space, but the tight binding of clotrimazole argues against this view. It appears that the heme distal pocket of PGIS is fairly adaptable to ligands of various structures. UV-visible absorption, magnetic circular dichroism and electron paramagnetic resonance spectra indicate that PGIS has a typical low-spin heme with a hydrophobic active site. PGIS catalyzes homolytic scission of the peroxide bond of a test substrate, 10-hydroperoxyoctadeca-8,12-dienoic acid, accompanied by formation of a heme intermediate with a Compound II-like optical spectrum.